Yield and quality of oat seed in function of date and plant density - Bobadilla Meléndez Mirna; Gámez Vázquez Alfredo J.; Ávila Perches Miguel A.; García Rodriguez Juan J.; Espitia Rangel, Eduardo; Moran Vázquez Nicolás; Covarrubias Prieto, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
The oat crop has great importance in Mexico, as it has increased its area planted in the last 15 years. In years with rainfed delay or long periods of drought, has promoted the planting of this cereal in extensive disaster areas, however, the seed supply is insufficient and its demand is so high, that promotes the trade of dubious quality seed. In Mexico there is still no technology for proper agronomic management to the production thereof. So the objective of this research was to evaluate the effect of planting date and density on yield, physical and physiological quality of the seed of four varieties, grown under irrigation in the Bajío Guanajuato, for which was used a split plot design. Planting dates were crucial for the expression of yield and physical quality of seed; however did not affect the physiological characteristics, the late date (December 31) gave the highest yield, however environmental conditions thereof adversely inf luenced volumetric weight. In seed density of 90 kg seed ha-1 obtained a good yield, volumetric weight and thousand kernel weight. The genetic constitution (varieties) showed the greatest differential response among the factors studied, besides being crucial in the expression of physiological seed quality (germination percentage, length of plumule and seedling dry weight). The variety Obsidian was the best in yield and seed quality.